Mass Media and Technology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The confluence of the mass media and technology has radically changed the patterns of media consumption and the media in general. This paper presents the changing nature of the relationship between the traditional and digital media with particular emphasis being given to how new digital technologies are ushering in the transformation of content creation, distribution, and viewer engagement. The mixed-method approach was used, which included a thorough literature review, qualitative content analysis and quantitative survey of consumers of media. The results show that there is a significant change in the traditional media sources including television and print media to the digital platforms including social media, streaming service and mobile application. There is a high inclination towards digital media among the consumers, especially the younger groups, which is aided by convenience, access, and personalization. The paper highlights the importance of media convergence and the diffusion of innovations in the discussion of such changes. Nonetheless, there are still gaps in the comprehension of how digital technologies transform the structural forces of the media industry, in the areas of advertising models, misinformation, and trust to the authorities. This research has far reaching consequences to media organizations, which need to adopt digital transformation as a way of remaining competitive. The ethical issue of digital media, economics of digital content production and the changing role of traditional media in influencing the public discourse should be researched in the future. This study is a contribution to the general knowledge on the convergence of mass media and technology and its suggestions are aimed at changing with the fast moving media world.